Hiding Multi Short Audio Signals in Color Image by using Fast Fourier Transform - M. Jamel, Enas (Al-Nahrain Journal of Science, 2021)
Many purposes require communicating audio files between the users using different applications of social media. The security level of these applications is limited; at the same time many audio files are secured and must be accessed by authorized persons only, while, most present works attempt to hide single audio file in certain cover media. In this paper, a new approach of hiding three audio signals with unequal sizes in single color digital image has been proposed using the frequencies transform of this image. In the proposed approach, the Fast Fourier Transform was adopted where each audio signal is embedded in specific region with high frequencies in the frequency spectrum of the cover image to save much more details of the cover image and avoid any doubts that there is any secret information are hidden inside it. The quality of the stego-image and the extracted audio files are evaluated with the standard evaluation metric. The simulation results shown significant results of these metrics and achieve good imperceptibility and high security of the stego-image. The SNR and SPCC values are considered acceptance that means significant in terms quality and similarity of the reconstructed signal.